Creation of BODIPYs-based red OLEDs with high color purity via modulating the energy gap and restricting rotation of substituents. (July 2022) - Ma, Daiyu; Zhao, Guimin; Chen, Haowen; Zhou, Renyin; Zhang, Guanghao; Tian, Wenwen; Jiang, Wei; Sun, Yueming
Abstract: At present, the investigation of luminescent materials with high color purity is becoming the hotspot domains, though red dyes and red solution-processed OLEDs are relatively scarce. Hence, three new BODIPY derivatives (BODIPYs) were designed and synthesized by modulating the energy gap (Eg ) and restricting rotation of substituents, namely B1, B2, and B3 . Encouragingly, B1, B2, and B3 exhibited red narrowband emission in toluene, with the maximum emission peaks and full width at half maxima (FWHM) of 607, 615, 624 nm and 35, 41, 41 nm, respectively. And systematic studies demonstrated that introduction of sterically hindered tert -butyl and o-methoxybenzene units can not only restrict the rotation of substituents by means of changing the dihedral angle at the connection sites, but also regulate the energy gap (Eg ) by fine-tuning the frontier molecular orbitals. Ultimately, the PhCz-4CzTPN was employed as the dendritic TADF sensitizer, and the solution-processed OLEDs based on B3 exhibited standard pure red emission with an EQEmax, an EL peak, a narrow FHWM, and Commission Internationale de l'Eclairage coordinates of 1.01%, 632 nm, 52 nm, and (0.67, 0.33), respectively. Graphical abstract: Fine-tuning the HOMO/LUMO of BODIPYs to achieve red emission while maintaining narrow-spectral emission, and the solution-proceed red TSF-OLEDs with high color purity were constructed based on BODIPYs, corresponding to an EQEmax, an EL peak, a narrow FHWM, and CIE coordinates of 1.01%, 632 nm, 52 nm, and (0.67, 0.33), respectively. Image 1 Highlights: Three new narrow-spectrum red BODIPYs were obtained. Introduction of substituents with steric hindrance can affect FWHM and energy gap. Red TSF-OLEDs showed an FHWM of 52 nm and CIE coordinates of (0.67, 0.33).